Anxiety Levels Of Primipara Mother With The Length Of Labor Progress In The First Active Phases At Community Health Centre Mataram City - Mila, Nirwana; Prabantoro, Benedictus TR; Wattimena, Inge (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Introduction: According to data from the Department of Health (2018) , infant mortality rate(IMR) in the first semester was as many as 10.294 cases, and the maternal mortality rate(MMR) in the first semester was as many as 1712 cases. Continuity and Duration of labor areessential factors in determining the number of IMR and MMR. Several factors affecting laborduration are power, passenger, passage, and maternity mother psychological. Purpose: To understand the correlation between primipara mothers' anxiety levels with thelength of labor progress in the first active phases. Method: This research used observational analytic method with a cross-sectional design anda purposive sampling technique. The research period was two months, with total respondentswere 40 people. Statistical analysis was done using Spearman rank correlation test. Results: 40 pregnant primipara mothers underwent labor at Mataram City CommunityHealth Centre in June - August 2019. We found about four respondents have heavy levels ofanxiety, in which all of them had no progress in delivery labor. Based on the statistical testsusing the spearman rank, there is a strong, positive (Ï€ = 0.714) and significant correlation (P =0,000) between anxiety level of primipara mothers with the length of labor progress in thefirst active phase. Conclusion: There is a significant correlation between primipara mother anxiety levels withthe period length of labor progress in the early active phases at Babakan community healthcenter Mataram City. Researchers have shown that the higher the anxiety level, the longer thelabor progress, and vice versa. This result must be explored further because of anxiety thataffects mothers' condition during labor and affects uterine contractions and cervical dilatationthat determine the smooth labor process.